Your livestock mapped out - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Mapping poverty and livestock in the developing world Published by the International Livestock Research Institute (ILRI), including a CD- ROM, 2002. 124 pp. ISBN 92 9146 109 1 Online version available at www.dfid.gov.uk and www.ilri.org